Ministerial advisers in executive government: Out from the dark and into the limelight. (13th June 2017) - Hustedt, Thurid; Kolltveit, Kristoffer; Salomonsen, Heidi Houlberg
Abstract : Ministers increasingly rely on advisers for support and advice. In many countries, these political aides are labelled differently. Generally, they serve as close confidants to their political masters and operate in the 'shadowland' between politics and bureaucracy. Scholarship has dragged the ministerial advisers out of the dark and described their background and functions. Still, the field of scholarship has a Westminster bias, is characterized by single case studies, and remains under‐theorized. The lack of comparative focus and theoretical underpinnings can be explained by the complex nature of ministerial advisers. This introductory article suggests a definition for ministerial advisers and reviews the extant literature on these important actors. The main argument is that the extent and relevance of ministerial advisers in executive government merits integration into mainstream public administration and political science theory and research.